Efektivitas Penggunaan Metode Qur’any dalam Memperlancar Membaca Al-Qur’an Siswa - Dita Dzata Mirrota; Ibnu Rusydi; Hervina Savitri (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2023)
Efforts to improve the ability to read the Qur'an in students certainly cannot be separated from the efforts of teachers and madrasahs who have a goal for the success of students. Because the ability to read includes skills that are learned intentionally, The purpose of this study was to find out how effective the Qur'anic method is for the fluency of reading the Koran for students at Segodorejo Middle School, Jombang. This study uses a quantitative method with a one shot case study research design. The sample used was class VII students, as many as 16 students. Data collection techniques in this study were carried out using psychomotor assessment sheets and documentation. After the data is collected, prior to analysis, the data normality test is first performed, and the sig value is obtained. of 0.354, then carried out a comparative test in the form of a one-sample T-test, obtaining a sig. of 0.000, which means less than a, which is 0.05. From the data, it is also known that the calculated t value is 14.158 for the previous value and 13.703 for the after value. Then the calculation of the t count and t table for the value before is 14.158 > 2.145, and the calculation of the t count and t table for the value after is 13.703 > 2.145, which means hypothesis 0 is rejected and hypothesis 1 is accepted. So it can be concluded that the use of the Qur'anic method has proven effective in facilitating students' reading of the Qur'an.